Genetics of head and neck cancer: Advances in molecular research (Research, Society and Development, 2022)
Most cases of head and neck cancer (HNC) originate from squamous cells and include tumors that arise in the epithelium of the nasal and oral cavity, paranasal sinuses, pharynx and larynx. More than half a million cases are diagnosed each year. The treatment for this neoplasm is considered a challenge, due to its intratumoral heterogeneity and the various anatomical subsites. In addition to genetic factors, it is also necessary to consider environmental components and gene-environment interactions, which can induce susceptibility to the disease. The main focus of therapies is to decrease side effects as well as increase the overall survival of patients. Due to the great complexity in tumor heterogeneity, a better understanding of the epigenetic mechanisms is of paramount importance for the development of therapies for this neoplasm. Given this context, this work aims to carry out a literature review regarding the genetics of head and neck cancer, as well as advances in molecular research. A total of 74 articles were selected, which provide a comprehensive view on the development of research aimed at clinical applications in diagnosis, prevention and treatment, whose research source was PubMed. According to the literature, the elucidation of the epigenetic and genetic mechanisms associated with carcinogenesis have a relevant role in the progression and response to treatment, the understanding of their participation may provide insights into their relationship in tumorigenesis, which are essential for precision medicine, contributing to personalized and patient-directed therapies.